Tempo de latencia do rocuronio e da succinilcolina e condicoes de intubacao traqueal - Vianna, Pedro Thadeu Galvão [UNESP]; Catiglia, Y. M M [UNESP]; Ganem, Eliana Marisa [UNESP]; Takata, I. H. [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Curi, P. R. [UNESP] (My University, 1997)
Background and Objectives - Pulmonary aspiration of gastric content during induction of anesthesia for emergency surgical procedures is a serious complication; fast endotracheal intubation under these circumstances is of vital importance to secure the airways. Despite its numerous side effects, succinylcholine is used for this purpose. Rocuronium is the most recently introduced aminoesteroid neuromuscular blocking drug with short onset. The objective of this study was to compare the onset time and intubating conditions of rocuronium and succinylcholine. Methods - After informed consent, forty-five patients were randomly allocated into three groups of 15: Group I (GI) = succinylcholine 1 mg.kg-1; Group II (GII) = rocuronium 0.6 mg.kg-1; Group III (GIII) = rocuronium 0.9 mg.kg-1. Every patient was premedicated with midazolam 15 mg per os and induction of anesthesia was made with fentanyl 10 μg.kg-1 and etomidate 0.3 mg.kg-1. The neuromuscular block was monitored with the TOP-Guard neuromuscular transmission monitor. The TOP-Guard neuromuscular monitor uses an accelerometer to measure the response to nerve stimulation. The stimulating electrodes were placed close to the course of the ulnar nerve at the wrist. The onset time was considered as the time between the end of neuromuscular drug injection and the twitch height (T1) decrease to 10%. Heart rate and arterial blood pressure were registered at 6 moments before and after induction of anesthesia. Results - The onset time results were: Group I, 71 s; Group II, 120 s and Group III, 70 s or GI = GIII < GII (F = 8.862; p < 0.01). There were 43 patients exhibiting excellent intubating conditions and 2 with good intubating conditions. Heart rate and arterial blood pressure showed alterations due to induction of anesthesia and intubation. Conclusions - Rocuronium 0.9 mg.kg-1 can be used in rapid sequence induction because it has a short onset time which is similar to that of succnylcholine. It is likely that rocuronium would be a good indication in patients with high intracranial pressure, burns and neuromuscular diseases.
Onset time and intubating conditions of rocuronium and succinylcholine
Keywords: Neuromuscular blockers: rocuronium, succinylcholine; fentanyl; midazolam; neuromuscular blocking agent; rocuronium; suxamethonium; anesthesia induction; arterial pressure; clinical article; clinical trial; controlled clinical trial; controlled study; heart rate; human; nerve stimulation; neuromuscular blocking; randomized controlled trial; side effect; ulnar nerve